Group II Introns: Highly Structured yet Dynamic - Esra Ahunbay; Susann Zelger-Paulus; Roland K. O. Sigel (CHIMIA, 2023)
RNA splicing, the removal of introns and ligation of exons, is a crucial process during mRNA maturation. Group II introns are large ribozymes that self-catalyze their splicing, as well as their transposition. They are living fossils of spliceosomal introns and eukaryotic retroelements. The yeast mitochondrial Sc.ai5γ is the first identified and best-studied self-splicing group II intron. A combination of biochemical, biophysical, and computational tools enables studying its catalytic properties, structure, and dynamics, while also serving to develop new therapeutic and biotechnological tools. We survey the history of group II intron studies paralleling the trends in RNA methodology with Sc.ai5γ in the spotlight.